Antimicrobial activity of Secondary Metabolites of fungi isolated from soil against selected pathogenic bacteria - Nadia Mubarik, Ghadir Ali, Muhammad Khrram, Aneeqa Sadiq, Ijaz Ahmad, Sidra Iqbal, Salman Hussain, Adnan Hussain Tanoli, Mir Sadiq Shah, Muneeba Wali (International Journal of Modern Agriculture, 2021)
Background: Due to the rise of drug-resistant bacteria, the need for novel antibiotics is growing by the day. Despite the abundance of possible antibiotic sources, such as medicinal plants, soil remains the most significant reservoir for new antibiotics with pharmacological and biological action. Objective: The goal of this research was isolation and identification of soil fungus, as well as to determine their antimicrobial activity against pathogenic microorganism. Methodology Soil samples were taken at several locations within the district of Mardan. The fungal isolates were sampled and isolated using the direct inoculation technique. Each fungal isolate was microscopically examined for identification. Secondary metabolites were extracted and chromatographic analysis was performed on all of the fungal extracts. The disc-diffusion technique was used to determine the antibacterial activity of secondary metabolites produced by isolated fungal strains according to previous study. Results: In our study, Aspergillus fumigates was isolated from soil samples. The various phytochemicals observed in A. fumigatus were tannins, flavonoids and terpenoids. 100 ÂµL concentration of the metabolite was used for antimicrobial activity. The zone of inhibition against Pseudomonas aeruginosa, E.coli, Staphylococcus aureus and Salmonella typhi were 19 mm, 20 mm, 18 mm, 19 mm respectively. Conclusion: The substantial genetic diversity identified in A. fumigatus strains might lead to the discovery of novel metabolites that could be used to generate new antibiotics.